2012
DOI: 10.3168/jds.2012-5594
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of intramammary infections with minor mastitis pathogens on the acquisition of new intramammary infections with major mastitis pathogens—A systematic review and meta-analysis

Abstract: Major mastitis pathogens such as Staphylococcus aureus, Streptococcus agalactiae, Streptococcus uberis, Streptococcus dysgalactiae, and the coliforms are usually considered more virulent and damaging to the udder than minor mastitis pathogens such as Corynebacterium bovis and coagulase-negative staphylococci (CNS). The current literature contains several studies detailing analyses with conflicting results as to whether intramammary infection (IMI) with the minor pathogens decreases, increases, or has no effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 39 publications
(40 reference statements)
1
49
0
13
Order By: Relevance
“…It has been suggested that presence of minor pathogens (non‐aureus staphylococci, corynebacteria) at the teat end may protect against infection with major pathogens (Reyher et al., ). The authors of a recent review (Reyher et al., ) concluded that observational studies showed no such effect, “whereas challenge studies showed strong and significant protective effects, specifically when major pathogens were introduced into the mammary gland via methods bypassing the teat end.” Physical or physicochemical characteristics of the teat end may contribute to that discrepancy, such as the amount of keratin present, peak flow rate and teat canal length (Capuco et al., ; Lacy‐Hulbert & Hillerton, ). In some modern large herds, for example, in the High Plains area of the western United States, milk production is measured per hour rather than per cow, acre or person.…”
Section: Disease In the Natural Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that presence of minor pathogens (non‐aureus staphylococci, corynebacteria) at the teat end may protect against infection with major pathogens (Reyher et al., ). The authors of a recent review (Reyher et al., ) concluded that observational studies showed no such effect, “whereas challenge studies showed strong and significant protective effects, specifically when major pathogens were introduced into the mammary gland via methods bypassing the teat end.” Physical or physicochemical characteristics of the teat end may contribute to that discrepancy, such as the amount of keratin present, peak flow rate and teat canal length (Capuco et al., ; Lacy‐Hulbert & Hillerton, ). In some modern large herds, for example, in the High Plains area of the western United States, milk production is measured per hour rather than per cow, acre or person.…”
Section: Disease In the Natural Hostmentioning
confidence: 99%
“…For most mastitis pathogens, the teat end is considered the porte d'entree into the mammary gland. It has been suggested that presence of minor pathogens (non-aureus staphylococci, corynebacteria) at the teat end may protect against infection with major pathogens (Reyher et al, 2012). The authors of a recent review (Reyher et al, 2012) concluded that observational studies showed no such effect, "whereas challenge studies showed strong and significant protective effects, specifically when major pathogens were introduced into the mammary gland via methods bypassing the teat end."…”
Section: Porte D'entreementioning
confidence: 99%
“…The most common causative agent of mastitis is Staphylococcus aureus (Contreras & Rodríquez, 2011;Makovec & Ruegg, 2003;Reyher et al, 2012;Wilson et al, 1997). It is an infectious bacterial pathogen, which is usually spread between cows during the milking process.…”
Section: Introductionmentioning
confidence: 99%
“…As bactérias S. aureus, S. agalactiae, S. dysgalactiae e S. uberis normalmente causam maiores danos ao úbere que outros patógenos causadores de mastite, e por isto são denominados patógenos principais ou maiores (Reyher et al, 2012). Entre os agentes causadores da mastite mais frequentemente isolados, são S. aureus e S. agalactiae, responsáveis por, aproximadamente, 90% das infecções intramamárias dos rebanhos de bovinos leiteiros.…”
Section: Prevalência Da Mastite Em Rebanhos De Bubalinosunclassified